Answer:
option a
Step-by-step explanation:
We will simply rearrange the equation for .
Therefore, option A is correct
Answer:
n=65th term
Step-by-step explanation:
AP:3,15,27,39......
From the AP
a=3
a+d=15
a+2d=27
3+d=15 (1)
3+2d=27 (2)
Subtract (1) from (2)
We have,
2d-d=27-15
d=12
54th term=a+(n-1)d
=3+(54-1)12
=3+(53)12
=3+636
=639
The term is 132 more than the 54th term
132+54th term
=132+639
=771
Find the term
771=a+(n-1)d
771=3+(n-1)12
771-3=12n-12
768=12n-12
768+12=12n
780=12n
n=780/12
=65
n=12
The term which is 132 more than the 54th term is the 65th term
1. a=0
2. b=2
3. b=-2
4. none of the above
Answer: The correct option is (2)
Step-by-step explanation: We are given to find the exclude value for the following algebraic expression:
We know that
for a rational expression, we must exclude those values for which the denominator of the fraction becomes zero.
So, in equation (i), the excluded value will be given by
Thus, the required excluded value is
Option (2) is CORRECT.
g(x) = 5x
Write the expressions for (f times g)(x) and (f+g)(x) and evaluate (f-g)(2)
Answer:
Step-by-step explanation:
a) fg(x)
--> f(5x)
--> 3(5x)+3
--> 15x+3
b) f+g(x)
--> 3x+3+ 5x
c) (f-g)(2)
3x+3- 5x
--> 3(2)+3-5(2)
--> -1
Answer:
solution given:
f(x) = 3x+3
g(x) = 5x
now
(f times g)(x)=?
(f+g)=?
(f-g)=?
we have
(f times g)(x)=f(g(x))
substituting value of g(x)
f(g(x))=f(5x)
now replacing value of x in f(x)
f(5x)=3(5x)+3
solving it
f(5x)=15x+3
so (f times g)(x) =15x+3
Step-by-step explanation:
again,
(f+g)(x)=f(x)+g(x)=3x+3+5x=8x+3
so
(f+g)(x) =8x+3
again
we need to find (f-g)(x) first so
(f-g)(x)=f(x)-g(x)=3x+3-5x=-2x+3
now
(f-g)(2)=-2*2+3=-1
(f-g)(2)=-1
The solution to the equation is .
To solve the equation log(x) + log(8) = 2, we can use the properties of logarithms.
The equation can be simplified using the logarithmicproperty:
Rewrite the equation in exponential form:
To solve for x, divide both sides of the equation by 8:
Therefore, the solution to the equation is .
To learn more on Equation:
#SPJ6